2004
DOI: 10.1177/1367493504041853
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Experiences of Caring for their Child Following Day Case Surgery: a Diary Study

Abstract: The development of children's health care over the last 15-20 years has resulted in an increased move towards ambulatory care, including day case surgery, which has implied benefits in reduced hospitalization and cost. The wider impact on the child and family is less clear. The study aimed for greater insight into the impact of day case surgery on the child and family from the parent's perspective. Using a qualitative approach and descriptive and inductive methods, the design focused on the parent's experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Separate diaries were developed for both children and parents to complete once a day following discharge from hospital. Diaries have proved to be an effective data collection method with adults (Jacelon and Imperio, 2005; Ritchie et al, 2000) and children (Bray, 2007; Hughes and Callery, 2004). Participants completed the diary for up to 1 week or until the child was ‘back to normal levels of activity’, as perceived by the child and parent.…”
Section: Methodsmentioning
confidence: 99%
“…Separate diaries were developed for both children and parents to complete once a day following discharge from hospital. Diaries have proved to be an effective data collection method with adults (Jacelon and Imperio, 2005; Ritchie et al, 2000) and children (Bray, 2007; Hughes and Callery, 2004). Participants completed the diary for up to 1 week or until the child was ‘back to normal levels of activity’, as perceived by the child and parent.…”
Section: Methodsmentioning
confidence: 99%
“…Although this issue has been raised in prior reviews (Burman, 1995;Maikler, 2000;Palermo, Valenzuela, & Stork, 2004), few research articles report the level of completion of the diary. In a qualitative study using diaries to assess postoperative care after day surgery, Hughes and Callery (2004) reported that diary entries varied considerably both in length of entries (1 to 20 pages total) and in the number of days completed (1 to 10 days). Data collection with diaries may have two sources of missing data: Entries may be incomplete or missing altogether.…”
Section: Diaries As a Data-collection Methodsmentioning
confidence: 99%
“…In these studies, data can be collected through follow-up phone calls, surveys, or diaries. Researchers have found diaries particularly useful for collecting descriptive data about the postoperative period (Finley et al, 1996;Hughes & Callery, 2004). Studies also have used the pain diary to ascertain differences between groups after pharmacologic or nonpharmacologic interventions (Fors, Sexton, & Götestam, 2002;Roy et al, 2004).…”
mentioning
confidence: 99%
“…Τα προγράµµατα προεγχειρητικής προετοιµασίας γονέων έχουν σκοπό να ελαττώσουν το γονικό άγχος, το οποίο εµφανίζεται σε µεγαλύτερο βαθµό στις µητέρες και αποτελεί µια σηµαντική παράµετρο µε συσχέτιση ευθέως ανάλογη µε το άγχος των παιδιών [60,77] . Η προετοιµασία των γονέων των οποίων τα παιδιά προγραµµατίζονται για χειρουργείο έχει ιδιαίτερη σηµασία και είναι αποτελεσµατικότερη αν προηγηθεί διαστήµατος 5-7 ηµερών από το χειρουργείο [61,62,71] .…”
Section: εικunclassified